Systemic Evaluation of Vocational Education Reform: A CIPP Analysis of Curriculum Implementation in Aceh - Zubaidah Zubaidah; Suraiya Suraiya; Abdul Manan; M Nur Akhyar (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2025)
This study examines the localized implementation of national vocational education reform, specifically focusing on the pedagogical shift within Technical and Vocational Education and Training institutions in Aceh, Indonesia. While curriculum transformation aims to address global 21st-century challenges, a gap remains in systemic evaluation within regions marked by geographical diversity and institutional disparities. Utilizing the Context, Input, Process, and Product (CIPP) model, this research employs a descriptive qualitative approach through policy document analysis and a systematic review of implementation reports. Findings reveal that while reform is urgent to bridge competency gaps, significant barriers persist in the input dimension, including uneven teacher readiness, inadequate infrastructure, and budget misalignments. In the process stage, student-centered learning remains inconsistent and largely performative, resulting in varied student outcomes where character-building and modern skill acquisition goals are not yet fully realized. The study concludes that 'one-size-fits-all' approaches are ineffective for diverse regional contexts. Practical implications necessitate differentiated support policies, localized teacher training, and a shift in supervision from administrative compliance to pedagogical substance